Pelaksanaan layanan informasi dalam menurunkan sikap positif siswa terhadap PCC - Hengki Satriana (Universitas PGRI SUMATERA BARAT, 2017)
Paracetamol, Caffeine, and Carisoprodol (PCC) case of drug abuse became one of the special concerns for the government. It needs counseling service to help students abstain from PCC abuse. One of the way that can be provided is through information services. This study is to aim whether information services are effective to reduce students' positive attitudes toward PCC. This research is a quantitative research with pre-experimental design method in the form of the one group pretest-posttest design. Data were collected using attitude scale. Data were analyzed descriptively and hypothesis tested by using t test. The result of this research is information service effective in reducing students' positive attitude toward PCC. Keyword : information service, PCC.